Oral health-related quality of life in children and dental anxiety of their caregivers Literature review - García Cárdenas, Jorge (2021)
It has been determined that the quality of life, as well as the habits that we may acquire during life, can affect in one way or another our quality of life, oral health, such as eating habits, socioeconomic differences and racial / ethnic, parental education and family structure, as well as the fear that parents or guardians project from previous experiences to their children who are just entering dental care on a more conscious level. The objective of this article is to review elementary concepts of oral health- related quality of life in children and its relationship with dental anxiety of their caregivers.